2.2' Bipyridine Catalyzed Peracetic Acid Bleaching of Cotton - Gürsoy, Nevin Çiğdem; Dayio, Habip (SAGE Publications, 2003)
Peracetic acid is produced directly in the bleaching liquor from acetic anhydride and hydrogen peroxide. The effects of process parameters (concentrations of hydrogen per oxide, acetic anhydride, treatment temperature, time, and pH) and also the interactions of the parameters as they affect the whiteness, bursting strength, and water absorbency of fabric, are investigated using a full factorial experimental design with Maximize 3.6 software, and the significance order of the process parameters is established. Then a central composite experimental design is used to determine an estimated optimized bleaching recipe with the help of the software. Estimated response values of the estimated optimized recipe are also obtained from the software, and the recipe is applied to cotton fabric samples. Measured response values of the applied optimized recipe show that the measured and estimated values are very close to each other.